Characterization of novel memory devices based on nanostructured materials - Win, Aye Sandar. (2012)
An Al-rich Al2O3 thin film was deposited on a p-tpye silicon substrate by radio frequency sputtering to form Al/Al-rich Al2O3/p-Si MIS diode. The current-voltage(C-V) characteristics of the diodes were determined by carrier injection from either the silicon substrate or the Al gate and by carrier transport along the tunneling paths formed by Al nanocrystals distributed in the oxide layer. The reverse I-V characteristics were greatly affected by the charge trapping in the oxide layer. However the charge trapping did not produce a large change in the forward I-V characteristic. The electrical characterization was performed on three samples with different annealing conditions and the memory effect was observed from measurement results analysis.